Construction of Legal Reform of The Transfer of Foreign Citizen Drug Crime Inmates to Their Home Countries Based on Aspects of Legal Certainty - Rusman Rusman; Faisal Santiago; Tina Amelia (Siber Nusantara Research, 2026)
This article develops a legal-certainty-oriented construction for Indonesia's forthcoming law on the transfer of sentenced persons (TSP), with specific attention to foreign nationals convicted of drug offences. Using a doctrinal legal method legislative, conceptual, and comparative approaches, the paper assesses Indonesia's current baseline (Article 45 of Law No. 22/2022 on Corrections), identifies implementation gaps in the absence of a specific statute, and draws comparative lessons from the Council of Europe Convention on the Transfer of Sentenced Persons (ETS No. 112), the EU Framework Decision 2008/909/JHA, and UN guidance (UNODC, International Guidelines on Human Rights and Drug Policy). Legal certainty is translated into eleven normative pillars: clear scope and definitions; material and formal requirements with explicit time limits; human-rights safeguards (non-refoulement, prohibition of torture, equality of treatment); designation of a central authority; calculation of remaining sentence and additional penalties; limited procedural review; drug-case-specific safeguards ensuring continuity of rehabilitation; diplomatic coordination and agreements; transparency and data protection; and transitional provisions. The proposed model enhances predictability, proportionality, and inter-jurisdictional consistency while aligning with contemporary human-rights-based drug policy. Policy implications are offered for Indonesia's ongoing legislative process (2023–2025).